Investigation of Serum Cartonectin Concentrations in Pregnant Women with Gestational Diabetes Mellitus; a Prospective Non-Interventional Cohort Study - Gebes, Onur; Kale, İbrahim and Beser Gebes, Tuba and Muhcu, Murat (Gynecology Obstetrics & Reproductive Medicine, 2024)
OBJECTIVE: To investigate serum cartonectin concentrations in pregnant women diagnosed with Gestational Diabetes Mellitus (GDM). STUDY DESIGN: This prospective non-interventional cohort study was conducted on 176 pregnant women. The study group consisted of 88 pregnant women diagnosed with GDM, and the control group consisted of 88 pregnant women with normal 75-g OGTT results. First, the study and control groups, and then the subgroups were compared in terms of serum cartonectin concentrations. RESULTS: The study and control groups were similar in terms of BMI and gestational age at blood sampling (p=0.599, p=0.854). The study and control groups were similar in terms of median serum cartonectin concentrations (6.28 ng/ml and 7.13 ng/ml, respectively, p=0.165). In the subgroup analysis, the normal weight control group, overweight control group, normal weight study group, and overweight study group were compared in terms of serum cartonectin concentrations. The lowest median cartonectin concentration was detected in the overweight study group, followed by the overweight control group, normal weight study group, and normal weight control group (5.8 ng/ml, 6.5 ng/ml, 6.9 ng/ml, and 8.2 ng/ml, respectively, p=0.235). CONCLUSION: Serum cartonectin concentrations were found to be similar in the GDM and control groups. However, the number of participants in this study is limited to draw a definitive conclusion. Many studies with larger series are needed to reveal whether serum cartonectin is involved in the pathophysiology of GDM.